2020
DOI: 10.1111/jssr.12639
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Religion and Spirituality: A Longitudinal Topic Modeling Approach

Abstract: In lieu of the traditional text data analysis methods, structural topic modeling was utilized to analyze the text contents of 255 self‐report inventories of religion and spirituality (R/S) published from 1929 to 2017. The study had two objectives: (a) to clarify and identify the latent dimensions of R/S inherent in the items of the measures; and (b) to examine and demonstrate the usefulness of a longitudinal topic modeling in the study of R/S. We identified 5,617 unique text terms from the measures and fitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 59 publications
0
31
0
1
Order By: Relevance
“…Researches on religion and spirituality have constantly expanded and being discussed in many publications (Koenig, 2012;Weaver et al, 2006). In fact, scholars from outside of behavioural, social and health sciences are familiar and engaged in religion and spiritual studies (Kim, et al, 2020). Spiritual wellbeing focuses on peace, stability and an intimate relationship with yourself and God, signifies two existential and religious dimensions.…”
Section: Covid-19 and Religiositymentioning
confidence: 99%
“…Researches on religion and spirituality have constantly expanded and being discussed in many publications (Koenig, 2012;Weaver et al, 2006). In fact, scholars from outside of behavioural, social and health sciences are familiar and engaged in religion and spiritual studies (Kim, et al, 2020). Spiritual wellbeing focuses on peace, stability and an intimate relationship with yourself and God, signifies two existential and religious dimensions.…”
Section: Covid-19 and Religiositymentioning
confidence: 99%
“…Social science researchers have argued that topic models may also be used as a novel means of examining linguistic framing/word choice (Valdez et al, 2018) and to track scientific fields and disciplines over time (Kim et al, 2020). To study framing, Valdez et al (2018) analyzed the 2016 U.S. presidential debate transcripts for linguistic differences between candidates Clinton and Trump.…”
Section: Applications In Health-related Fieldsmentioning
confidence: 99%
“…Yet when discussing these topics, the phraseology (i.e., words used) by each candidate differed, reflecting their divergent positions on the issues. Kim et al (2020) used a longitudinal topic modeling approach to examine the content of various religion and spirituality inventories over nearly a century, from 1929 to 2017. While the authors found three primary topics across all inventories tested, they found that one (Experience of Transcendence) was relatively rare in early inventories but increasingly common over time.…”
Section: Applications In Health-related Fieldsmentioning
confidence: 99%
“…According to Bornet and others (16) spirituality, that is, the feeling of believing that there is a greater power beyond the environment of human reach and other dimensions such as purpose, meaning of life, awareness of personal resources and the deepest feelings, personal integrity or connectedness. The scopes of spirituality consist of three dimensions (17), namely the meaning of life reflects the meaningfulness of life or the purpose of one's life. Peace is an effective aspect of one's spirituality and beliefs, including the individual's comfortable feelings that come from connecting with something broader than the human self (18,19).…”
Section: Covid-19 Virus and Religiositymentioning
confidence: 99%